Retinal inflammation diagnosed as an idiopathic macular hole with multiple recurrences and spontaneous closures: A case report. Issue 4 (January 2019) - Hayashi, Isami; Shinoda, Hajime; Nagai, Norihiro; Tsubota, Kazuo; Ozawa, Yoko
Abstract: Rationale: An idiopathic macular hole that causes substantial reduction in central visual acuity is believed to involve no obvious underlying diseases; thus, it is suspected to form due to the presence of idiopathic tractional forces at the vitreoretinal interface. Importantly, it is effectively treated with pars plana vitrectomy (PPV), which removes the mechanical forces. However, while it is exceedingly rare, a macular hole can develop in eyes after PPV; fresh or postoperative macular holes can close spontaneously without surgical removal of traction. Thus, another mechanism might be involved, although it remains obscure. Patients concerns: A 67-year-old woman experienced 4 episodes of distorted and/or blurred vision. Diagnosis: She was diagnosed with recurrent macular hole formation. Interventions: For each episode, she either underwent surgery or was placed under observation. Outcomes: The macular hole was twice closed with PPV and twice without. The 2nd PPV procedure, which was performed at the time of 2nd recurrence, confirmed the absence of the epiretinal membrane and internal limiting membrane that cause tractional forces at the vitreoretinal interface in the macular area. At the time of the 3rd recurrence, fluorescein angiographies (FAs) revealed the presence of mild and diffuse inflammation throughout the peripheral retina, although there were no other findings indicative of ocular inflammation during the general eye examination conducted for every episode of macular hole formation. After the initiation of topical steroid treatment, inflammation (as recorded on FA) was reduced, and the macular hole subsequently closed. Development and resolution of perifoveal cystoid change and retinal protrusion were observed in every episode in optical coherence tomography (OCT) images. A bridging element in an OCT image was observed during the 4th closure of the macular hole. Lessons: Dynamic changes in FA and OCT images unraveled the pathogenesis of a macular hole that was originally diagnosed as idiopathic; mild inflammation was involved. The FA is typically not used for the diagnosis and management of macular hole formation; however, its use in this case helped determine a new mechanism in an otherwise idiopathic disease.